Hadith #3509 - Sunan Abi Dawud - Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Muslim bin Khalid al-Zanji مسلم بن خالد الزنجي; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
I and some people were partners in a slave. I employed him on some work in the absence of one of the partners. He got earnings for me. He disputed me and the case of his claim to his share in the earnings to a judge, who ordered me to return the earnings (i.e. his share) to him. I then came to Urwah ibn az-Zubayr, and related the matter to him. Urwah then came to him and narrated to him a tradition from the Messenger of Allah (ﷺ) on the authority of Aisha: Profit follows responsibility.
Grade: Hasan